Breaking The Cycle: Maternal Knowledge, Sanitation, dan Diarrhea Prevention in Toddlers - widya fadhilascha; Danny Wresniwira Danandjaja; Ronald Pratama Adiwinoto; Retno Wisanti (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2026)
This research aims to explore the relationship between maternal knowledge and sanitation hygiene with the incidence of diarrhea in young children within the Socah Community Health Center's service area. The study employs a quantitative approach with an observational cross-sectional design. Primary data was gathered using a questionnaire assessing maternal knowledge and daily sanitation hygiene practices. Data analysis was conducted using both univariate and bivariate methods, including the chi-square test. The findings reveal that, among 101 mothers with toddlers who met the inclusion criteria, most had low knowledge (40.6%) and moderately implemented hygiene and sanitation practices (37.6%). Additionally, 47.5% of the children had experienced diarrhea in the past two weeks. The chi-square test showed a significant correlation between maternal knowledge and the occurrence of diarrhea (p < 0.001), as well as between hygiene and sanitation practices and the incidence of diarrhea in children (p < 0.001). The study concludes that both maternal knowledge and sanitation hygiene significantly affect the occurrence of diarrhea in children in the Socah Community Health Center area. It is recommended that health education regarding diarrhea prevention, personal hygiene, and environmental sanitation be enhanced to reduce diarrhea rates among infants. This research is intended to serve as a foundation for the planning of health support and prevention programs in the Community Health Center's service area.